2008
DOI: 10.2217/14622416.9.6.691
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphism Analysis of CYP2C19 in Chinese Han Populations from Different Geographic Areas of Mainland China

Abstract: This is the first study that systematically screened the polymorphisms of the whole CYP2C19 gene in a large Chinese Han population. The results suggest that a few low frequent variants show significant differences among the four populations, while the prevalent polymorphisms show no differences. Therefore, our database provides important information on CYP2C19 polymorphisms in the Chinese population, and could be helpful for future personalized medicine studies in Asian populations generally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(65 citation statements)
references
References 32 publications
5
60
0
Order By: Relevance
“…Comparing allele frequencies of our Han samples (Beijing) with five other geographical subpopulations of Han Chinese (Hong Kong, Shanghai, Shantou, Shenyang and Xi'an), 10,12,20,35 we observed that the frequencies of three major alleles of CYP2C19 (*1, *2 and *3) are significantly (Po0.05) different from that of Shengyang and Xi'an subpopulations. Furthermore, four major alleles of CYP2D6 (*1, *2, *5 and *10) vary significantly (Po0.05) against the five other subpopulations.…”
Section: Q Zhou Et Almentioning
confidence: 67%
See 1 more Smart Citation
“…Comparing allele frequencies of our Han samples (Beijing) with five other geographical subpopulations of Han Chinese (Hong Kong, Shanghai, Shantou, Shenyang and Xi'an), 10,12,20,35 we observed that the frequencies of three major alleles of CYP2C19 (*1, *2 and *3) are significantly (Po0.05) different from that of Shengyang and Xi'an subpopulations. Furthermore, four major alleles of CYP2D6 (*1, *2, *5 and *10) vary significantly (Po0.05) against the five other subpopulations.…”
Section: Q Zhou Et Almentioning
confidence: 67%
“…Furthermore, genetic compositions in Han Chinese are complex. Thus, although some previous work has been done, [10][11][12][20][21][22] it is quite worthwhile to investigate variants of the aforementioned two genes for Han Chinese. In our study, we intensively screened for genetic variants of CYP2C19 and CYP2D6 in Han Chinese, systematically analyzed the linkage disequilibrium (LD) and haplotype structure of these two genes, and computationally predicted the functions of novel polymorphisms.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous samples were recruited from Shanghai, the southern part of China, whereas the samples in the present study were collected from Xi'an, the northern part of China. Many studies found that a cryptic borderline was observable between the Southern Han and the Northern Han samples [17][18][19]. Thus, population regions may influence the data.…”
Section: Controlmentioning
confidence: 99%
“…Pronounced ethnic differences exist in the frequencies of the non-functional alleles: a low frequency of up to 5% in the Caucasian and African populations, higher in Oriental populations (23%). CYP2C19*2 and CYP2C19*3 are together responsible for the majority of PM alleles, of which CYP2C19*3 is mainly found in Asians (Chen et al, 2008;Xie et al, 2001). …”
Section: Cyp2c19mentioning
confidence: 99%